Emergency Department Interventions for Older Adults: A Systematic Review. Issue 7 (15th March 2019) - Hughes, Jaime M.; Freiermuth, Caroline E.; Shepherd‐Banigan, Megan; Ragsdale, Luna; Eucker, Stephanie A.; Goldstein, Karen; Hastings, S. Nicole; Rodriguez, Rachel L.; Fulton, Jessica; Ramos, Katherine; Tabriz, Amir Alishahi; Gordon, Adelaide M.; et al.
Abstract : OBJECTIVES: To evaluate the effect of emergency department (ED) interventions on clinical, utilization, and care experience outcomes for older adults. DESIGN: A conceptual model informed, protocol‐based systematic review. SETTING: Emergency Department (ED). PARTICIPANTS: Older adults 65 years of age and older. METHODS AND MEASUREMENT: Medline, Embase, CINAHL, and PsycINFO were searched for English‐language studies published through December 2017. Studies evaluating the use of one or more eligible intervention strategies (discharge planning, case management, medication safety or management, and geriatric EDs including those that cited the 2014 Geriatric ED Guidelines) with adults 65 years of age and older were included. Studies were classified by the number of intervention strategies used (ie, single strategy or multi‐strategy) and key intervention components present (ie, assessment, referral plus follow‐up, and contact both before and after ED discharge ["bridge"]). The effect of ED interventions on clinical (functional status, quality of life [QOL]), patient experience, and utilization (hospitalization, ED return visit) outcomes was evaluated. RESULTS: A total of 2000 citations were identified; 17 articles describing 15 unique studies (9 randomized and 6 nonrandomized) met eligibility criteria and were included in analyses. ED interventions showed a mixed pattern of effects. Overall, there was a small positive effect of ED interventions on functional status but no effects on QOL, patient experience, hospitalization at or after the initial ED index visit, or ED return visit. CONCLUSION: Studies using two or more intervention strategies may be associated with the greatest effects on clinical and utilization outcomes. More comprehensive interventions, defined as those with all three key intervention components present, may be associated with some positive outcomes.